2018
DOI: 10.1002/pssa.201800529
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of All-Optical Logic Gate Device Using MQW-SOA and 10 Gbps XNOR Operation

Abstract: All-optical logic gate device as a label recognition device for all optical packet networks, which is integrated with a multi-quantum-well semiconductor optical amplifier (MQW-SOA) and double micro-ring resonators (MRRs) is proposed. The nonlinearity of an MQW-SOA such as cross-gain modulation (XGM) and four-wave mixing (FWM) is investigated, and the operation conditions of the input powers and the wavelengths are clarified for efficient XGM and FWM operation. On the basis of these conditions, all-optical XNOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The structure of the SOA in conjunction with the optical fiber is limited to the high-speed because of the phase recovery characteristics and the slower gain. Therefore, the MZI is the right choice to overcome the limitation of the high bit rates [15,16].…”
Section: Soa Non-linearitymentioning
confidence: 99%
“…The structure of the SOA in conjunction with the optical fiber is limited to the high-speed because of the phase recovery characteristics and the slower gain. Therefore, the MZI is the right choice to overcome the limitation of the high bit rates [15,16].…”
Section: Soa Non-linearitymentioning
confidence: 99%
“…The all-optical non-inverted parity generator and checker based on SOAs is shown in Figure 1. From the principle of the optical generator and checker circuit, we found that it can be composed of XOR [14][15][16] and XNOR [17,18] gate, the dotted line section, and the entire working in Figure 1 correspond to the parity generator and checker, respectively.…”
Section: Principlementioning
confidence: 99%
“…Due to the integration of potential and good non-linear characteristics of semiconductor optical amplifiers, people have a strong research interest. There are extensive studies in all-optical signal processing and all-optical calculations, such as switches, clocked flip-flops [13], logic gates [14][15][16][17][18], subtracter and adder [19][20][21][22], decoder/encoder [20,23], and comparator [23,24]. It can be seen from the research of various all-optical technologies that semiconductor optical amplifiers have broad application prospects in future optical communication systems.…”
Section: Introductionmentioning
confidence: 99%